Editing 3D models on smart devices. (February 2015) - Kang, Yuna; Kim, Hyungki; Suzuki, Hiromasa; Han, Soonhung
Abstract: This study proposes a 3D CAD system available on smart devices, which are now a part of everyday life and which are widely applied in various domains, such as education and robot industry. If an engineer has a new idea while traveling or on the move, or in the case of collaboration between more than two engineers, this 3D CAD system allows modeling to be performed in a rapid and simple manner on a smart device. This 3D CAD system uses the common multi-touch gestures associated with smart devices to keep the modeling operations simple and easy for users. However, it is difficult to input the precise geometric information to generate 3D CAD models by such gestures. It is also impractical to provide a full set of modeling operations on a smart device due to hardware limitations. For this reason, the system excludes several complicated modeling operations. This work provides a scheme to regenerate a parametric 3D model on a PC-based CAD system via a macro-parametrics approach by transferring the 3D model created on a smart device in an editable form to a PC-based CAD system. If fine editing is needed, the user can perform additional work on a PC after reconstruction. Through the developed system, it is possible to produce a 3D editable model swiftly and simply in the smart device environment, allowing for reduced design time while also facilitating collaboration. This paper discusses the first-ever system design of a 3D CAD system on a smart device, the selection of the modeling operations, the assignment of gestures to these operations, and use of operation modes. This is followed by an introduction of the implementation methods, and finally a demonstration of case studies using a prototype system with examples.